The factors which influences people to do bribe in organization / Dhabitah Abdullah Thani and Nabila Shuhada Bashari - Abdullah Thani, Dhabitah; Bashari, Nabila Shuhada (Faculty of Business and Management, 2014)
This paper consists of studies about the bribery which happened nowadays. The purpose of this study is to conduct the survey on the factory workers in Goodyear Malaysia Berhad regarding the “Factors Influencing People to Bribe”. Our study basically based on Goodyear Malaysia Berhad’s factory workers which include the various departments which consist of administration, manufacturing and the factory workers itself. In addition, for this research, we use primary data in order to collect the reliable data from the questionnaire that will be answer by the respondents. In addition, the entire questionnaire was been distributed among the factory workers at Goodyear Malaysia Berhad at Shah Alam. The problem statement of these studies is Malaysia has been ranked as one of the most corrupt nations and listed as a country which is most likely to take shortcuts to meet targets when economics times are tough. In fact, Malaysia along China has the highest levels of bribery and corruption everywhere in the world. Based on the study, there are four (4) factors that will influence the bribery which is attitude of the workers, the culture of the workers, financial stability of the workers and the social influences that affect the workers to do bribe. From the findings, the most influences factor effect bribe is social influences. One of the recommendations that can be made is the Ministry of Finance should be aware and do more observations regarding the bribery problem and try do something that can give awareness about bribe towards employees.